METODE GARIS SINGGUNG DALAM MENENTUKAN HAMPIRAN INTEGRAL TENTU SUATU FUNGSI PADA SELANG TERTUTUP [????, ????] (Universitas PGRI Sumatera Barat, 2010)
There is a value of Riemann integral from a function that cannot becalculated. In this case, approximate method can be used to interpret the value.One of the approximate method of integral Riemann is tangent line method that isa compound method between the sum of Riemann and trapezoid method. Thetangent line method uses the tangent line approach. In this writing, the topicdiscussed is the tangent line method in deciding the approximacy of Riemannintegral of a function.